Polityka jako wyraz służby człowiekowi i społeczeństwu - Jan Dyduch (Polonia Sacra)
The teaching of the Church presents a compact system of political activity, whose task is to care for the common good of individuals, families and associations. Political activity in the country should be based on ethical principles deriving from justice, love and religious liberty. The State and the Church, serving the same people, are obliged to cooperate. Such cooperation can be expressed in the agreement, called the concordat.